2016
DOI: 10.18632/oncotarget.13658
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma midkine and pleiotrophin levels in patients with systemic lupus erythematosus

Abstract: Emerging evidence suggests that two heparin-binding growth factor, midkine and pleiotrophin are implicated in the pathogenesis of autoimmune diseases including SLE. To investigate the plasma midkine and pleiotrophin levels in SLE patients, as well as their correlation with major clinical parameters and interleukin-17 (IL-17) level in SLE, 83 SLE patients and 123 controls including 20 rheumatoid arthritis (RA) patients, 21 Sjögren's syndrome (SS) patients and 82 healthy controls (HCs) were recruited. Plasma mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
2
9
1
Order By: Relevance
“…Our result was consistent with Wu et al that there was no significant difference in serum Midkine levels in SLE patients with and without the renal disorder (P > 0.05). But, there was a significant difference in serum Midkine levels between flare and remission in our result (P = 0.018) contrary to a previous study (P > 0.05) [ 17 ]. In Rheumatoid Arthritis (RA), Shindo et al reported that MK level could be a biomarker of RA disease activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our result was consistent with Wu et al that there was no significant difference in serum Midkine levels in SLE patients with and without the renal disorder (P > 0.05). But, there was a significant difference in serum Midkine levels between flare and remission in our result (P = 0.018) contrary to a previous study (P > 0.05) [ 17 ]. In Rheumatoid Arthritis (RA), Shindo et al reported that MK level could be a biomarker of RA disease activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Our result was comparable to a study conducted by Wu GC et al, that reported median Midkine levels were 698.37 (516.09-767.07) pg/ml and 628.22 (373.66-712.41) pg/ml in SLE patients and healthy control group. Our study result was consistent with Wu GC et al that Midkine serum levels were significantly increased in SLE patient (P < 0.05) [ 17 ]. Elevated Midkine serum level also occurs in other autoimmune diseases such as rheumatoid arthritis and multiple sclerosis [ 10 ] [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Increased levels of MK in autoimmune and inflammatory diseases have been shown in prior reports Our result was consistent with Salama et al which reported that MK levels in patients with Alzheimer's disease, as another neurological disease, is more than healthy persons (10). Plasma MK was elevated in patients with systemic lupus erythematosus which was correlated with IL-17 (11). In rheumatoid arthritis (RA) patients, high MK levels were found to implicated in the pathogenesis of RA and was associated with IL-6 and IL-8 (12,13).…”
Section: Discussionsupporting
confidence: 91%
“…We previously reported elevated plasma MK and PTN concentrations in SLE compared with healthy controls, and the increase in MK and PTN levels correlated with inflammatory cytokine IL-17 and some clinical features/parameters, including rash and anti-SSA antibody, suggesting that an aberrant expression of MK and PTN might be involved in the progress of inflammation and the course of SLE (25).…”
Section: Discussionmentioning
confidence: 90%
“…In rheumatoid arthritis (RA), a study has found an increased serum MK level in RA patients and its correlation with disease activity score (DAS) 28-erythrocyte sedimentation rate (ESR) and rheumatoid factors (RFs) titer (24). Our previous study has revealed that, as compared to healthy controls, the levels of plasma MK and PTN are elevated in SLE and also associated with interleukin (IL)-17 levels and some clinical manifestations, including rash and anti-Sjögren's-syndrome-related antigen A (anti-SSA) (25). These findings suggest a potential role of MK and PTN involved in certain types of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 98%